The association between sleep patterns and overweight/obesity in Chinese children: a cross-sectional study - Zhang B (Dove Medical Press, 2015)
Bin Zhang,1,* Yanli Hao,2,* Jiangyan Zhou,1,3 Fujun Jia,1 Xueli Li,1 Yi Tang,1 Huirong Zheng1 1Guangdong General Hospital, Guangdong Academy of Medical Sciences, Guangdong Mental Health Centre, 2Department of Human Anatomy, Guang Zhou Medical University, 3Department of Psychiatry, Southern Medical University, Guangzhou, People’s Republic of China *These authors contributed equally to this work Objective: This study evaluated the association between sleep patterns and the risk of being overweight/obese in Chinese children. Methods: A total of 3,086 children (1,608 boys and 1,478 girls) between 7 and 14 years of age and studying in primary schools were recruited as eligible study participants in this study. We collected the information about children regarding sleep patterns, body height and weight, insomnia, healthy status, time allocation of daily activities, and demographic characteristics using a parental-reported questionnaire. Results: Overweight/obese children were younger, predominantly male, and more prone to have suffered from illness in the past 12 months compared to normal-weight peers. They were also less prone to compensate for sleep deficits during weekends (47.6% vs 39.1%; χ2=11.637, P<0.001) and holidays (52.0% vs 42.0%; χ2=16.057, P<0.001). Sleep duration on weekdays did not affect the risk of being overweight/obese. The adjusted odds ratios for overweight/obesity (noncompensated) group using the compensated group as a reference were 1.197 (95% confidence interval [CI]: 1.004–1.493) during weekends and 1.309 (95% CI: 1.052–1.630) during holidays. Conclusion: Compensation for sleep deficits on non-weekdays may ameliorate the risk of being overweight/obese in Chinese children. Moreover, no significant association between the risk of being overweight/obese and sleep duration on weekdays was demonstrated in the current study, which may be due to pervasive sleep insufficiency on weekdays in Chinese children. Keywords: Chinese children, overweight/obese, sleep duration, sleep compensation